Gramsci's pathways - Liguori, Guido (Leiden ; Boston : Brill, 2015)
Gramsci's works, in particular his 'Prison Notebooks', are a real 'workshop' of activity. Even though these texts were the product of a great mind and an organic conception of the world, the particular context in which they are written poses challenges for their interpreters. This philological 'excavation' of the pathways of Gramsci's thinking brings us closer to an author who is more 'widely-known' than he is understood. The first part of the volume deals with central themes of Gramsci's worldview such as the concepts of the state, civil society, ideology, common sense, morality and conformism. The second part deals with Gramsci's relations with thinkers as diverse as Marx, Engels, Togliatti and Labriola, whereas the third part offers some reflections on the metaphors used by Gramsci as well as contemporary views of the Sardinian Communist. 0First published in Italian by Carocci as 'Sentieri gramsciani', 2006.
"First published in Italian by Carocci Editore as "Sentieri gramsciani", Biblioteca di testi e studi, Rome, 2006."
Includes bibliographical references (p. 223-231) and index.
Keywords: Gramsci, Antonio, -- 1891-1937.; Gramsci, Antonio, -- 1891-1937.; Gramsci, Antonio, -- 1891-1937.; Quaderni del carcere (Gramsci, Antonio)